GLANDULAR AND EXTRAGLANDULAR MANIFESTATIONS IN PATIENTS WITH SJÖGREN'S SYNDROME AND THEIR CORRELATION WITH IMMUNOLOGICAL PARAMETERS - Đokić, Ivana; Djokic, Ana; Djokic, Milena; Raskovic Ivic , Sanvila (Medicinski podmladak, 2025)
Introduction: Sjögren’s syndrome (SS) is a chronic systemic autoimmune disease. The disease spectrum extends from sicca syndrome to systemic involvement and extraglandular manifestations. Patients with SS present a broad spectrum of serologic features. Certain serological findings are highly correlated with specific clinical features, and can be used as prognostic markers.The Aim of this paper was analysis of glandular and extraglandular clinical manifestations of primary SS (pSS) and their association with laboratory findings.Material and Methods: The research was conducted as a retrospective cross-sectional study involving 30 patients with pSS hospitalized at the Clinic for Allergology and Immunology University Clinical Center of Serbia in Belgrade. Demographic, clinical and laboratory  characteristics of patients were analyzed, as well as  association between them.Results: Dry eyes and mouth were experienced by all subjects included in the study. Arthralgia and/or myalgia were the most common extraglandular manifestation of pSS, which was present in all patients. This was followed by: chronic fatigue (83.3%), skin manifestations (66.67%), neuropsychiatric manifestations (60%), Raynaud's phenomenon (40%), gastrointestinal manifestations (33.3%), thyroid (26.67%), and respiratory disorders (23.3%). Paraprotein was identified in 13.33%, and proteinuria in 10% of patients. Antinuclear antibodies (ANA) were positive in 80%, anti-Ro/SSA in 76.67%, anti-La/SSB in 20%, and RF in 16.67% of patients. Raynaud's phenomenon was associated with the presence of chronic fatigue (p=0.047), gastrointestinal with neuropsychiatric manifestations (p=0.017), and chronic fatigue was also associated with involvement of exocrine glands of other locations (except lacrimal and salivary glands). Thyroid dysfunction was inversely associated with SSB antibody findings (p=0.024).    Conclusion: Dry eyes and mouth, arthralgia and/or myalgia were the most common manifestation of pSS. ANA and SSA antibodies were the most common immunoserological findings. There was no statistically significant association of any examined immunoserological findings with the presence of glandular and extraglandular manifestations of pSS.Keywords: Sjögren's syndrome; glandular features; extraglandular features; ANA; anti-Ro/SSA; anti-La/SSB
Keywords: Sjögren's syndrome; glandular features; extraglandular features; ANA; anti-Ro/SSA; anti-La/SSB